PENGARUH PENGGUNAAN LEMBAR KERJA SISWA (LKS) DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS SMA NEGERI 3 KOTA JAMBI - Sondang Purba; Diliza Afrila (Universitas Batanghari Jambi, 2020)
This study aims to determine the effect of using Student Worksheets (LKS) and the independent learning outcomes of students in economic subjects in class X IPS SMA Negeri 3 Jambi City. The results showed that (1) the use of student worksheets (LKS) did not have a significant effect on student learning outcomes. Based on the results of data analysis, it is known that the value of tcount < ttable (1.441 <1.659). Furthermore, the variable contribution of using Student Worksheets (LKS) to student learning outcomes is 11.7%. (2) Independent learning has a significant effect on student learning outcomes. Based on the results of data analysis, it is known that the value of tcount > ttable (1.937 > 1.659). Furthermore, the contribution of the independent learning variable to student learning outcomes is 19.2%. (3) The use of student worksheets (LKS) and independent learning has a significant effect on student learning outcomes in economic subjects in class X IPS at SMA Negeri 3 Jambi City. Based on the results of data analysis, it is known that the value of Fcount > Ftable (3.166> 3.04). Furthermore, the variable contribution of the use of student worksheets (LKS) and independent learning to learning outcomes was 36.4%.